Hydraulic design of a diversion weir - Sanpet Jansong; Prida Thimakorn; Preecha Kamronrithisorn; Wang, Tsan-Wen; Loof, Rainer; The Government of the Republic of Korea (Bangkok : Asian Institute of Technology, 1987)
Research and development to increase the efficiency of water use and to reduce the problem of water shortages is an ongoing activity in a large number of irrigation projects. However, there are many constants in the development of Large Scale Irrigation Projects (LSIP ), and Medium Scale Irrigation Projects (MSIP), therefore, further development in Small Scale Irrigation Projects (SSIP) is necessary. One example of an SSIP is the diversion and inundation scheme , where a regulating weir in a natural stream raises the water level and diverts it to the area requiring . The amount of funds made available for SSIP is limited and this is reflected in less attention to accuracy of water level control , less effective operation and scouring in the downstream channel. As the demand for SSIP is high, a standard design f or such weirs to overcome these limitations. It is at this stage that this study is made . This study has investigated May son's weir and modified weirs through laboratory experiments. The investigation was divided into two parts , i.e. the characteristics of flow through the weir, and the energy dissipation. Scour in the downstream channel bed was investigated in order to determine the geometry of the stilling basin which gives the most effective energy dissipation. From the study, it was found that i ) application of a flap gate in a small weir results in better flow release comparing with Mayson ' s weir , ii) operation for controlling water level s upstream can be pre- de t ermined, iii) lowering the bas in floor and adjustment of floor blocks can reduce the downstream bed erosion to an appreciable level , and iv) the generalized design criteria provides a convenient tool in t he design process in small weirs. A standardized design of flap gate weir is also presented in this study.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1987
Keywords: Weirs; Hydraulic structures; Hydraulic models